A MOLECULAR AND CLINICAL STUDY OF PROTEUS MIRABILIS ISOLATED FROM HUMAN - Essmaa Hussein Gutef; Zinah Shakir Shallal; Dunya Talib Mahdi (European Science Publishing, 2024)
To the family Enterobacteriaceae, Proteus mirabilis belongs as a Gram-negative bacterium. It causes a wide range of infections, including those of the genitourinary system, the respiratory system, the skin, and diabetic foot ulcers. Antibiotic-resistant bacteria are becoming more commonplace around the world. Proteus mirabilis has been found to be highly resistant to many antibiotics, which raises the risk of the development of multidrug resistance and treatment failure. In this investigation, Proteus mirabilis isolates were recognized using conventional biochemical techniques. The sensitivity test were used to determine antibiotic resistance while the PCR tests were performed with primers that were designed to bind to the ureR gene, which encodes the urease enzyme that is a virulence factor of P. mirabilis. All Proteus mirabilis isolates tested positive for the ureR gene, and the resulting amplicon length was 225 base pairs. We collected swabs from several body sites, including urine, wounds, burns, genitalia, ears, eyes, and sputum. The tetracycline showed 100% resistance. Toxicity to tetracycline, ampicillin, ampicillin-sulbactam, and sulfamethoxazole-trimethoprim was extremely high. The antibiotics cefepime, cefotaxime, ceftazidime, and cefoperazone were all shown to have intermediate resistance. The levels of resistance to piperacillin, amikacin, and aztreonam were rather low. 87.2% of the isolates showed MDR (multidrug resistance). The development of antibiotic-resistant microorganisms is directly attributable to the careless overuse of these drugs. Patients' access to antibiotics should be restricted by strict restrictions. Antibiotics can't be given out until susceptibility testing has been completed. Furthermore, our findings suggest that the ureR and based PCR method is a valid technique for characterizing Proteus mirabilis.
Keywords: Proteus mirabilis, molecular, human.